A statistical look at the chromosome characteristics of Centaurea L. taxa distributed in Eastern Anatolia (Turkey) - Mikail Açar; Neslihan Taşar (Caryologia, 2022)
This study performed statistical analyses based on chromosome micromorphology of 18 Centaurea taxa, two of which are endemic. In addition, according to the data obtained from these analyses, the relationships between taxa and sections were tried to be interpreted. As a result of the analyses, the taxa C. drabifolia and C. kotschyi and C. behen and C. polypodifolia var. pseudobehen  were located close to each other. These taxa are located in the same sections in the morphological classification. Besides, in the discriminant analysis, the taxa of Acrocentron, Microlophus, Cheirolepis sections were closely located compared to all other taxa. However, results were not seen to cover all taxa of the sections.This study revealed various chromosomal characteristics of Centaurea taxa distributed in Eastern Anatolia. It also performed statistical analyses on these data. It revealed that comparing chromosomal calculations separately in taxa would be more beneficial in morphological classification than classifying them together into analysis structures.